Designing Porous Polymer Systems for Water Treatment Applications - Crawford, Ethan (University of Waterloo, 2025)
Increasing pollution and contamination of the World’s water bodies come with great concern over potable water safety and accessibility. Current solutions for water treatment often have large carbon footprints or are too expensive to scale up effectively. These shortcomings warrant the exploration of new and effective methods of water treatment. Polymer-based solutions offer lightweight, scalable, and inexpensive methods for water filtration while being minimally intrusive to the surrounding environment. In particular, porous polymeric materials have garnered considerable attention due to their high specific surface area, which enables them to have enhanced interactions with their target analyte. This thesis presents two such types of porous materials: nonwoven fabrics and three-dimensional (3D) printed filters. The first section of this thesis focuses on nonwovens, a type of fabric comprised of bonded, interlocking, randomly oriented fibers. Nonwovens can be used as topically placed sorptive mats for the removal of pollutants, or as a pass-through filter for the separation of water from the pollutants. Here, the unique oil gelation properties styrene-ethylene-butylene-styrene (SEBS) block copolymer are leveraged for the creation of melt-blown nonwovens for oil-water separation applications. The poor processability of SEBS, due to its elastomeric nature, was overcome through highly optimized processing parameters to create fine diameter, highly porous nonwoven mats. These mats possessed exceptional lipophilicity and oil-water separation properties due to the oil-soluble midblocks of SEBS that created a semi-solid gel capable of retaining all oil it came into contact with. The latter section of this thesis focuses on 3D printing, specifically fused deposition modelling (FDM), for the creation of flow-through filters for microplastic capture. 3D-printed parts are often very smooth, greatly limiting their surface area and ability for microplastics to become lodged on their surface. To overcome this, a sacrificial additive was added to the base polymer matrix that could be etched out, creating a highly porous surface that greatly improved the filtration efficiency of the printed filters. Pressure-sensitive adhesives (PSAs) were also explored and were found to further bolster the filtration capabilities of the filters. This is due to the added tack and non-covalent interactions that more strongly hold microplastics to the surface of the filters. The findings from these studies demonstrate a promising direction for utilizing porous polymer systems in water treatment applications.